An Unusual Presentation of Baker’s Cyst Rupture in an Inflammatory Bowel Disease Patient - Gianna Stoleru; Lauren George; Raymond K. Cross; Uni Wong (Case Reports in Medicine)
When evaluating a patient with acute onset unilateral leg pain and concurrent inflammatory bowel disease (IBD), keeping a broad differential diagnosis will allow for prompt diagnosis and management. The patient described in this case report is a 32-year-old male with inflammatory ileocolonic Crohn’s disease (CD) status after ileocecectomy with perianal involvement and known Type 1 arthropathy. He presented with a three-day history of unilateral leg swelling and tenderness. Initial evaluation focused on possible thrombosis given the development of erythema and systemic symptoms. Final diagnosis was ruptured Baker’s (popliteal) cyst. This pathology is not well described in existing literature, but should be considered in IBD patients given their chronic inflammatory state and common associated intra-articular pathology.